Proliferation Pattern of Pediatric Tumor-Derived Mesenchymal Stromal Cells and Role in Cancer Dormancy: A Perspective of Study for Surgical Strategy - Pelizzo, Gloria; Riva, Federica; Croce, Stefania; Avanzini, Maria Antonietta; Acquafredda, Gloria; de Silvestri, Annalisa; Mazzon, Emanuela; Bramanti, Placido; Zuccotti, Gianvincenzo; Mazzini, Giuliano; Calcaterra, Valeria (Frontiers in Pediatrics, 2021)
The explanation for cancer recurrence still remains to be fully elucidated. Moreover, tumor dormancy, which is a process whereby cells enter reversible G0 cell cycle arrest, appears to be a critical step in this phenomenon. We evaluated the cell cycle proliferation pattern in pediatric tumor-derived mesenchymal stromal cells (MSCs), in order to provide a better understanding of the complex mechanisms underlying cancer dormancy. Specimens were obtained from 14 pediatric patients diagnosed with solid tumors and submitted to surgery. Morphology, phenotype, differentiation, immunological capacity, and proliferative growth of tumor MSCs were studied. Flow cytometric analysis was performed to evaluate the cell percentage of each cell cycle phase. Healthy donor bone marrow-derived mesenchymal stromal cells (BM-MSCs) were employed as controls. It was noted that the DNA profile of proliferating BM-MSC was different from that of tumor MSCs. All BM-MSCs expressed the typical DNA profile of proliferating cells, while in all tumor MSC samples, ≥70% of the cells were detected in the G0/G1 phase. In particular, seven tumor MSC samples displayed intermediate cell cycle behavior, and the other seven tumor MSC samples exhibited a slow cell cycle. The increased number of tumor MSCs in the G0–G1 phase compared with BM-MSCs supports a role for quiescent MSCs in tumor dormancy regulation. Understanding the mechanisms that promote dormant cell cycle arrest is essential in identifying predictive markers of recurrence and to promote a dedicated surgical planning.